ECOTHEOLOGY-BASED ENVIRONMENTAL AWARENESS HABITUATION: AN ISLAMIC EDUCATION MANAGEMENT APPROACH IN FACING THE GLOBAL CRISIS - Evi Septiana Farida; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze and formulate an ecotheology-based management model for environmental awareness habituation as a strategic solution framework for Islamic educational institutions in responding to the threat of the global climate crisis. This study employs a qualitative approach with a library research design. The primary and secondary data sources are focused on reputable journal articles and authoritative texts discussing Islamic education management and environmental theology. Data were collected through literature documentation, analyzed using a descriptive-critical content analysis technique, and validated through literature source triangulation. The findings indicate that the habituation of environmental care character cannot grow organically; rather, it requires systemic intervention by integrating prophetic values into the four management functions (POAC). The formulated model encompasses: strategic planning based on the khalifah fil ardh vision, organizing through green leadership as a collective amanah, actuating zero waste routines as an implementation of macro thaharah, and controlling that converts physical punishment into ecological sanctions based on the principles of hisab and muraqabah. In conclusion, this "Ecotheology Habituation Management" governance framework is able to deconstruct institutional paradigms to transform religious dogma into concrete, structured, institutionalized, and sustainable earth-saving actions